Strengthening Tuberculosis Prevention Cadres at Al-Hidayah Islamic Boarding School, Kota Baru Jambi - Astuti, Erwin Hari; Krisdiyanta, Krisdiyanta; Tarigan, Ramly (PT FORMOSA CENDEKIA GLOBAL, 2024)
Possible risk factors for tuberculosis include population factors (age, sex, nutritional status, family role, income level, education level), home environment factors (ventilation area, occupancy density, lighting intensity, floor type, house humidity, temperature and wall type), behavior (habit of opening windows every morning and smoking habit) and contact history. According to WHO, adolescents are residents in the age range of 10-19 years, according to the Indonesian Minister of Health Regulation Number 25 of 2014, adolescents are residents in the age range of 10-18 years and according to the Population and Family Planning Agency (BKKBN) the age range of adolescents is 10-24 years and unmarried. There is a risk of transmission to students at the Al-Hidayah Modern Islamic Boarding School located on Jl. Marsda Surya Dharma KM. 10 Kenali Asam Bawah Jambi City.